Investigation of the causal relationship of saturated fat acids on heart stroke: evidence from two-sample Mendelian randomization - Danial Habibi; Iman Hamraz; Farshad Teymoori; Amir Hesam Saeidian; Hanifeh Mirtavoos-Mahyari; Qumars Kasnavi; Alireza Soleymani Taloubaghi; Homayoon Masoudi; Fereidoun Azizi; Maryam Sadat Daneshpour; Mehdi Hedayati; Mahdi Akbarzadeh; et al. (BMC Nutrition)
Abstract Background/Aim We conducted the Mendelian Randomization (MR) analysis to investigate the causal relationship between serum saturated fatty acids (SFAs) and the risk of heart stroke (HS). Methods The MRC-IEU Consortium provided summary statistics datasets related to SFAs, encompassing 64,979 individuals of European descent. Genetic variants associated with HF were identified using a GWAS dataset comprising 461,880 participants (cases = 7,055, controls = 454,825) of European descent from the UK Biobank. Generalized summary Mendelian Randomization (GSMR) assessed the potential association. Additionally, we performed a two-sample Mendelian Randomization (TSMR). The odds ratio (OR) with 95% confidence intervals (CIs) was indicated. Results The GSMR results suggested no significant between SFA and HS [OR = 1.002, 95% CI: 0.995, 1.009; P-value = 0.752]. TSMR revealed [ORIVW = 1.005, 95% CI: 0.998, 1.012; P-value = 0.169]. MR Egger (Q = 6.14, Q_pvalue = 0.292), IVW (Q = 6.24, Q_pvalue = 0.396; I2 = 18.7%) for heterogeneity test, and Egger intercept = 1.14 × e-4, p-value = 0.792 for pleiotropy test were performed. These findings remained consistent across various Mendelian Randomization methods, including IVW [OR = 1.005, 95% CI: 0.99–1.01, p-value = 0.169], Simple median [OR = 1.009, 95% CI: 0.99–1.02, p-value = 0.08], MR-Egger [OR = 1.001, 95% CI: 0.97–1.03, p-value = 0.97], Robust Adjusted Profile Score [OR = 1.005, 95% CI: 0.99–1.01, p-value = 0.167], MR-Lasso [OR = 1.005, 95% CI: 0.99–1.01, p-value = 0.169], Constrained maximum likelihood (MR-cML) [OR = 1.006, 95% CI: 0.99–1.01, p-value = 0.168], Weighted mode [OR = 1.01, 95% CI: 0.99–1.02, p-value = 0.279], Maximum-likelihood method [OR = 1.005, 95% CI: 0.99–1.01, p-value = 0.158]. Conclusion Our MR study did not yield convincing evidence supporting the association of SFAs with HF risk. Future studies should focus on alternative approaches to investigate this association.